In Vitro Activity Test Of Murayya Koenigii L. Spreng Leaves As A Natural Preservative For Tilapia Fish Meat - Su'adah Su'adah; Vivi Mardina; Fadliani Fadliani (Universitas Serambi Mekkah, 2021)
Fish that are high in protein content are prone to quality degradation. This is strongly thought to be due to the influence of microbes that are inside or outside the fish's body. The use of formalin for food preservatives is not recommended because it can interfere with health. In Indonesia, there are many natural preservatives that are safer to use, such as Murayya koenigii L. Spreng which is rich in antioxidants and has antibacterial properties. This study aimed to evaluate the effect of M. koenigii leaf extract as an inhibitor of bacterial growth in Oreochromis. niloticus fish meat and to measure the maximum concentration of M. koenigii leaf extract. The study used a completely randomized design method (RAL) with one factor, namely the concentration of temurui leaf extract (Murayya koenigii L. Spreng) which consisted of concentrations of 0, 10, 20, 40% (g / mL). The data were taken on storage time, namely 0 days, 1 day, 2 days, and 3 days. The observation parameter used was the inhibition zone diameter (mm) which was analyzed using one way ANOVA. The results showed that temurui leaves have the potential to be used as an inhibitor of microbial growth in O. niloticus fish meat at a concentration of 40% (g / mL) which is the maximum concentration.